WP1-9 Treatment implications of parkinson's disease in normal pressure hydrocephalus. Issue 3 (14th February 2019) - Funnell, JP; Craven, CL; D'Antona, L; Thorne, L; Watkins, LD; Toma, AK
Abstract : Objectives: Patients with Parkinson's disease (PD) presenting with worsening gait and ventriculomegaly could have underlying normal pressure hydrocephalus (NPH). We aim to identify features of concurrent PD and NPH, assess investigations and benefits of intervention. Design: Single-centre retrospective cohort study of patients diagnosed with PD and NPH, presenting to neurosurgery between April 2004 – April 2018. Subjects: 24 patients (20M: 4F) with concurrent PD and NPH, mean age 74.5±6.49 years (mean ±SD). 22 patients were diagnosed with PD prior to NPH diagnosis. Methods: Medical records were studied for demographics, symptoms, and response to ventriculoperitoneal (VP) shunting. Chi-square test was used to compare frequency of post-operative symptoms against a local database of NPH patients. Results: All patients presented to neurosurgery with gait disturbances, 21/24 with cognitive impairment, and 18/24 with urinary incontinence. 19 patients underwent VP shunt insertion; 5 patients were not suitable having failed a lumbar drain trial. Patients with PD and NPH improved in walking test outcomes and in urinary continence similarly to other NPH patients. Cognitive impairment did not respond well to VP shunting in patients with concurrent PD, significantly less than NPH patients without PD (p<0.01). Conclusions: Diagnosis of NPH in patients with PD is a complex clinical problem due to frequent overlap of symptoms. Benefits may be gained if this subset of patients do reach neurosurgical services and receive intervention.